Assessment of Neuropsychological Parameters of Graphomotor Skills among Children - Vasileva, Neli (Current Progress in Medicine and Medical Research Vol. 2, 2023)
This chapter highlights about dynamics of Neuropsychological Parameters of Graphomotor Skills in Typically Developing Children. Due to their rise in prevalence among children of school age, the issue of specific learning disorders is becoming more pertinent. There aren't enough discussions about how to prevent them, which accounts for the scant research on preschoolers who are set to start school. For the purpose of determining age norms for the development of fundamental mental abilities as well as anticipating potential literacy-related challenges, it is crucial to define their neuropsychological profiles. From a child neuropsychology perspective, the question of the development of graphomotor abilities as a fundamental precondition for learning has been extensively studied. A wide spectrum of specialists in the field of atypical and typical child development are becoming more interested in neuropsychological research as a result of the considerable theoretical, diagnostic, and practical advancements made in child neuropsychology in recent years. The reason for this is that the preschool period has a specific sensitivity to the specialization of the cerebral hemispheres and the formation of the morpho-functional basis of higher psychic functions. Graphomotor skills are a basic phenomenon in preschool age, and their development implies a complex integration of programming, executive and spatial functions. Children with typical development exhibit varying levels of graphic skills determined by the influence of social conditions and individual dynamics in the development of brain mechanisms of motor programs. Age plays a major role in the development of cerebral mechanisms and the dynamics of graphomotor functions during the preschool periodCriteria for outcome assessment included quality of serial movement organization, state of executive functions (mastery, degree of program formation), visual-spatial organization, and motor pauses. The analysis of the influence of the three independent factors on children's graphomotor functions shows the leading importance of the age factor for their development, which confirms the first hypothesis.The pooled individual group scores were subjected to analysis of variance, which showed statistically significant influence of all three factors: age, demographics, and gender. It is confirmed that children's graphomotor skills exhibit positive age dynamics, peaking around age 5. Only 18% of children at age 6 were totally skilled in the graphic test, despite a tendency towards progress in serial organization and coordination of motor movements. Separating subgroups by graphomotor ability level and various levels of school preparation is based on the stark disparities in individual results. The age period 4 - 6 years is sensitive for the formation of the serial and spatial organization of children's graphic skills as predictors of successful school learning. The "Fence" graphomotor exam is a convenient and objective way to diagnose complicated motor functions in preschoolers as well as a way to spot kids who may have learning issues in the future.